2019
DOI: 10.1667/rr15391.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relative Biological Effectiveness of Neutrons across Organs of Varying Depth among the Atomic Bomb Survivors

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Both populations also include study members with potential for exposure to neutrons, although in INWORKS, quantitative estimates of neutron dose were not available for all cohorts in all partner countries. Further attention to neutron dose estimation remains an important goal; a recent analysis reported that the relative biological effectiveness (RBE) value of neutrons in the LSS could range between 25 and 80 depending on the target organ, which is much higher than the value of 10 currently used in the calculation of the weighted absorbed dose (Cordova and Cullings 2019). In INWORKS, however, neutrons are thought to contribute a relatively small component to the collective dose (Thierry-Chef et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Both populations also include study members with potential for exposure to neutrons, although in INWORKS, quantitative estimates of neutron dose were not available for all cohorts in all partner countries. Further attention to neutron dose estimation remains an important goal; a recent analysis reported that the relative biological effectiveness (RBE) value of neutrons in the LSS could range between 25 and 80 depending on the target organ, which is much higher than the value of 10 currently used in the calculation of the weighted absorbed dose (Cordova and Cullings 2019). In INWORKS, however, neutrons are thought to contribute a relatively small component to the collective dose (Thierry-Chef et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…LSS neutron RBE dependence in the LSS risk models, upon which the RADS calculations are based, is accounted for here with an empirical LSS neutron RBE model (Hafner et al 2021 ). This model allows the application of an LSS neutron RBE value of 80, as indicated by Cordova and Cullings ( 2019 ) and other comprehensive studies cited therein, rather than the RBE of 10 usually applied in most official analyses of the LSS data (e.g., Preston et al 2007 ; Grant et al 2017 ; Cahoon et al 2017 ; Hsu et al 2013 ). When all other factors are equal, the behaviour of decreasing cumulative risk estimates obtained using LSS risks per unit LSS doses calculated as the LSS neutron RBE increase from 10 to 80, allows longer space missions within given risk limits of radiological protection.…”
Section: Discussionmentioning
confidence: 99%
“…The current methodology allows a user-based choice because this previous work has been extended and an LSS neutron RBE model has been recently developed (Hafner et al 2021 ) and applied here. An LSS neutron RBE value of 80 is applied here for the purposes of illustrating this HRA methodology, since Cordova and Cullings ( 2019 ) and other comprehensive studies cited therein, found indications that the LSS neutron RBE for colon dose is 80 (95% CI 20; 190), i.e., much higher than the value of 10 usually applied in most official analyses of the LSS data. The impact of uncertainties in the LSS neutron RBE can be assessed by running the prototype risk calculation software with different values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deterministic effects that are now commonly referred to as ''tissue reactions'' (e.g., radiation-induced tissue damage) and stochastic effects (e.g., cancer and genetic risks), which occur due to exposure to different types of radiation, are quantified into an empirical value known as the RBE. The relative effects of different neutron energies are often characterized by their RBE versus photon exposures, a ratio that changes based on different biological end points, neutron energy and neutron dose (3). The neutron energy spectrum and neutron dose will depend on the type of nuclear detonation and the shielding experienced by those exposed; therefore, RBE factors for neutrons need to be quantified.…”
Section: Stakeholder Interests and Needsmentioning
confidence: 99%